Mental Predicate KNOW Subtypes KNOW and FEEL in Japanese: Natural Semantic Metalanguage - Sukma, Luh Putu Ratnayanti (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 1 No 2 (2019)DO - 10.24843/JS.2019.v01.i02.p02, 2019)
Goddard and Wierzbicka (2014) mentions the original meanings of mental predicate consisting of six types namely think, know, feel, see, hear, want and don't want . This finding was forwarded into Japanese by Asano Cavanagh (2015), and found 12 verbs of Japanese language that were matched with those found by Goddard and Wierzbicka (2014). Of the twelve mental predicates that were continued by Asano, the type KNOW is matched with the verb ? ? shiru in Japanese. KNOW ?? shiru has subtypes KNOW and SAY. Furthermore, the subtype has three sub-subtypes, namely KNOW and SAY SOME, KNOW and SAY ALL PARTS, and KNOW and SAY AT ALL (NO).